OʻQUVChILARNI EKOLOGIK TARGʻIBOTChILIK FAOLIYATIGA TAYYORLAShNING PEDAGOGIK-PSIXOLOGIK XUSUSIYATLARI VA OMILLARI - Xojanov, B.K. (SCIENCE and SOCIETY, 2025)
The article examines the pedagogical and psychological characteristics also factors of preparing students for environmental propaganda activities in secondary educational institutions, as well as the implementation of work to involve schoolchildren in environmental activities.
Keywords: environmental education; environmental literacy; ecological culture; ecological intelligence; knowledge and faith; ecological potential; ecological knowledge; environmental propaganda